Minimization of ecological damage with the flood of petroleum products in the airport - Yа. I. Kochergin (Научный вестник МГТУ ГА)
The article examines the need for taking measures for warning and overcoming the consequences of the floods of oil and petroleum products, protection of population and natural environment from their harmful effect, as well as the minimization of ecological damage. The analysis of basic measures for the use of oil is carried out.